Role of Technological Acquisition and R&D Expenditure in Innovative Investment - Weiyu, Zou; Othman, Aniza; Guli, Tang (Frontiers in Psychology, 2022)
The current study examined the role of technological acquisition and research and development(R&D) expenditure in innovative investment. Technological acquisition and R&D are two crucial indicators of digital innovation. Therefore, to understand this, the current study collected data using questionnaire from 341 employees of R&D department in corporate sector of China. Data analysis was performed using structural equation modeling (SEM) technique. Smart-PLS was used for this purpose. A significant relationship between technological acquisition and research and development with innovative investment and attitude towards digital innovation was found. The study also found that attitude towards digital innovation among the employees positively and significantly impact innovative investment. Moreover, attitude towards digital innovation acts as a partial mediator between technological acquisition and innovative investment and also between research and development and innovative investment. Furthermore, technological culture moderated the relationship between technological acquisition and innovative investment but did not moderate the relationship between research and development and innovative investment. The use of the technology must be made common by providing training to the employees so that the technological skills of the employees can be polished and be utilized for the betterment of the firm. Furthermore, the study fills the gap in literature by providing and comprehensive model relating the research and development expenditure and technology acquisition to the innovative investments of the corporate sector.